Novel salep‐based chelating hydrogel for heavy metal removal from aqueous solutions. (11th February 2016) - Soleyman, Rouhollah; Pourjavadi, Ali; Monfared, Aazam; Khorasani, Zahra
Abstract : A novel optimized chelating hydrogel was synthesized via graft copolymerization of acrylamide and 2‐hydroxyethyl methacrylate (as two‐dentate chelating co‐monomer) onto salep (a multicomponent polysaccharide obtained from dried tubers of certain natural terrestrial orchids) using N, N ′‐methylenebisacrylamide as a crosslinker and ammonium persulfate as an initiator. Reaction parameters ( N, N ′‐methylenebisacrylamide and ammonium persulfate amounts as well as acrylamide/2‐hydroxyethyl methacrylate weight ratio) affecting the water absorption of the chelating hydrogel were optimized using a systematic method to achieve a hydrogel with high swelling capacity as possible. Heavy metal ion adsorption capacity of the optimized hydrogel for metal ions [Cu (II), Pb (II), Cd (II), and Cr (III)] were investigated in aqueous media containing different concentrations of these ions (5–50 ppm). The results showed that the hydrogel have great potential for heavy metal removal from aqueous solutions. The hydrogel formation was confirmed by Fourier transform infrared spectroscopy, and surface morphology study of the hydrogel was performed by scanning electron microscope. Copyright © 2016 John Wiley & Sons, Ltd.